2022
DOI: 10.1017/jfm.2022.184
|View full text |Cite
|
Sign up to set email alerts
|

Transient wave-induced pore-water-pressure and soil responses in a shallow unsaturated poroelastic seabed

Abstract: An analytical solution is developed for studying transient water wave-induced responses inside an unsaturated poroelastic seabed of finite thickness. The soil skeleton and the pore fluid are compressible and the constitutive relationship of the soil skeleton is described by Hooke's law. Assuming that the horizontal length scale of wave motion is much larger than the seabed thickness, the leading-order analytical solutions for the seabed responses, including pore fluid pressure and soil skeleton motion, are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Two wave-induced seabed liquefaction mechanisms, namely oscillatory and residual, have been reported in the literature [3][4][5]. The former is caused by oscillatory or transient excess pore pressures with phase lag and amplitude attenuation [6][7][8][9][10][11][12], while the latter is the result of the build-up of excess pore pressures due to soil contraction under cyclic loading [4,13]. This study considers both mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…Two wave-induced seabed liquefaction mechanisms, namely oscillatory and residual, have been reported in the literature [3][4][5]. The former is caused by oscillatory or transient excess pore pressures with phase lag and amplitude attenuation [6][7][8][9][10][11][12], while the latter is the result of the build-up of excess pore pressures due to soil contraction under cyclic loading [4,13]. This study considers both mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…(1992) was later extended by Gratiot and Mory (2000) to include the effect of water depth variations. Tong and Liu (2022) continued this work by presenting an analytical solution for the pore pressures within an unsaturated poroelastic seabed under transient waves, where previous studies had assumed simple harmonic waves acting on the seabed. They found that both the potential and duration of various seabed failures, including ML, are highly dependent on sediment properties, such as the saturation degree, the shear modulus, and the sediment permeability.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the analytical solution for the dynamic response of seabeds subjected to seawater waves has been widely studied (Ulker et al 2 ; Ulker 3 ; Zhou et al 4 ; and Tong and Liu 5 ). Many researchers have discussed the influence F I G U R E 1 Schematic of a seawater-sloping seabed-bedrock system.…”
Section: Introductionmentioning
confidence: 99%